Task instructions modulate the attentional mode affecting the auditory MMN and the semantic N400 - Erlbeck, Helena; Kübler, Andrea; Kotchoubey, Boris; Veser, Sandra (Frontiers in Human Neuroscience, 2014)
Event-related potentials (ERP) have been proven to be a useful tool as a complement to clinical assessment and to detect residual cognitive functions in patients with disorders of consciousness. These recordings of ERPs are often made using passive or unspecific instructions. Patient data obtained this way are then compared to data from healthy participants, which are usually recorded using active instructions. The present study investigates the effect of attentive modulations and particularly the effect of active versus passive instruction on the ERP components mismatch negativity (MMN) and N400. Eighteen healthy participants listened to three auditory paradigms: oddball, word priming and a sentence paradigm. Each paradigm was presented three times with different instructions: ignoring auditory stimuli, passive listening and focused attention on the auditory stimuli. After each task, the participants indicated their subjective effort. In general, the investigated ERP components decreased from the focused attention task to the passive task and from the passive task to the ignore task. Subjective effort was equally high in the passive and focused attention conditions but reduced in the ignore condition. We conclude that passive listening during EEG recording is stressful and attenuates ERPs, which renders the interpretation of the results obtained in such conditions difficult.